Nilai Anak Autis Menurut Alkitab dan Implikasinya Bagi Keluarga dan Sekolah - Saut Tua Pardomuan Sihombing Sihombing; Slamet Triadi (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2022)
Children with autism generally experience disturbances/ delays in development which will continue into adulthood if not treated seriously from an early age. Not all parents and families can accept the existence of this child. Therefore, parents must have learned to understand, accept, and teach/ educate their children. Parents who have autistic children should realize that their children are a gift. God still loves them. God never disparage children (Matt. 19:13; Mark 10:13-16). Likewise, they should realize that the children they have are God’s perfect creations (Gen. 13:31). This writing used a descriptive analysis method to explain autistic children, the difficulties faced by parents who have autistic children, and explain the importance of attitudes that must be possessed in teaching their children. The results of this study are: First, autistic children are children who experience developmental disorders which result in being unable to communicate and cannot express their feelings and desires. Second, children with autism need extra attention compared to children in general. Third, parents need to have patience, love and remain faithful in teaching children at home, knowing the principles of learning for autistic children, and knowing how their children learn.